A111 THE CANADA-GLOBAL RATING SCALE: USE OF AN INNOVATION LEARNING COLLABORATIVE METHODOLOGY TO GUIDE PROVINCIAL IMPLEMENTATION IN ALBERTA. (4th March 2021) - Sadowski, D; Oilund, C; Moysey, B; Greenaway, M; Jelinski, S; Morrin, L; McInnis, N; Nemecek, N; Snider, J; Underwood, F; Wong, C; Veldhuyzen Van Zanten, S
Abstract: Background: The Canada-Global Rating Scale (C-GRS) is a web-based, patient centered endoscopy quality improvement tool. It assesses the quality of the services an endoscopy unit provides in two dimensions: clinical quality and the quality of the patient experience. It also allows each endoscopy unit to choose priority areas for future QI activities. Scores are submitted twice a year to a centralized website by the local endoscopy site's C-GRS working group. Uptake of the C-GRS in Alberta has been historically poor with only 22/50 sites submitting a C-GRS survey in 2016. A provincial C-GRS project team was formed in 2018 to spearhead provincial implementation of the C-GRS. Alberta Health Services approved a C-GRS policy in 2020 mandating regular use of the C-GRS in all provincial endoscopy units. Aims: The purpose of this project is to describe a process of focused C-GRS implementation using Innovation Learning Collaborative (ILC) methodology. Methods: An ILC is a process meant to drive clinical pathway practice changes to achieve system-wide improvements. Inter-professional teams meet at least three times over a 12–18 month period at Learning Sessions to share successes, learnings, resources and data. A balanced scorecard (Figure 1) is used to track C-GRS progression and regression. Action Period meetings are held in between the Learning Sessions to help build collaboration and support the teams. Results: The first of three in-person ILC Learning Sessions was successfully held on November 29, 2019. 37 out of 50 sites in Alberta attended. Each site committed to working on up to 6 C-GRS descriptors during the course of the ILC. An updated scorecard is provided after each C-GRS cycle. An average of 25 sites attended Action Period meetings to report on progress and to share learnings with other sites. 44 endoscopy sites submitted a follow-up C-GRS survey in the spring 2020 cycle (an increase of 22 from 2016). 84% of sites demonstrated improvement with the average number of items improved at 5.1 Conclusions: Use of ILC methodology with a balanced scorecard approach can achieve system level improvement within a relatively short time frame. Funding Agencies: None